P52 New treatment guideline of Neisseria gonorrhoeae and test of cure: how feasible is it?. (23rd May 2012) - Rodgers, S; Murgartroyd, M; Perez, K; Kingston, M; Lee, V
Abstract : Background: Treatment failure with oral cephalosporins in gonorrhoea caused by multidrug resistance has been reported. The national guidelines were updated in 2011 due to reduced sensitivity to antimicrobials. Test of cure (TOC) is recommended in all cases. However data regarding timing of TOC is limited. Aims: To assess (1) the feasibility of implementing new treatment regimen and (2) the optimal time to perform TOC. Method: Retrospective case note review of patients diagnosed with gonorrhoea in a GUM clinic between 1 June 2011 and 30 November 2011 was carried out. Data including demographics, HIV status, sites of infection, treatment and TOC were analysed. Results: 271 (242M, 29F) patients were included. 202 were men who have sex with men (MSM) of which 24% were HIV positive. In MSM group, 87 were urine TMA positive (95% had cultures performed), 115 positive pharyngeal TMA (97% with cultures done), 115 positive rectal TMA (96% had cultures done). 39 heterosexual males had positive urine TMA (94% with cultures done). 18 (62%) females had positive cervical TMA, all with culture performed. 12 (41%) pharyngeal, 5 (17%) vulvo-vaginal and 3 (10%) rectal were TMA positive; 58%, 60%, and 33% of these had cultures performed respectively. First-line treatment was given in 96% of cases. Second line treatments were given mostly due to penicillin allergy. TOC was attended by 55% of patients. 67% of TOC were done within 20 days of treatment. Three of these were positive, 2 within 20 days and one at 57 days post treatment which was a re-infection. Conclusions: New treatment of gonorrhoea is generally accepted by patients. 4% received alternative treatments, which were valid and documented. The majority of patients (74%) had culture performed prior to treatment. TOC uptake was low (55%). However the majority were performed within 20 days of treatment. Follow-up strategies must remain a priority to increase rates of TOC. Further studies are required to determine optimum time for TOC.